2022
DOI: 10.1038/s41467-022-34403-5
|View full text |Cite
|
Sign up to set email alerts
|

The Neo-PLANET phase II trial of neoadjuvant camrelizumab plus concurrent chemoradiotherapy in locally advanced adenocarcinoma of stomach or gastroesophageal junction

Abstract: The synergistic effect of neoadjuvant immunotherapy and chemoradiotherapy in gastric adenocarcinoma is unclear. This phase II trial (NCT03631615) investigated this neoadjuvant combination in locally advanced adenocarcinoma of stomach or gastroesophageal junction. Thirty-six patients received capecitabine 850 mg/m2 twice daily and simultaneous radiotherapy for 5 weeks, sandwiched by a 21-day cycle of oxaliplatin 130 mg/m2 (day 1) plus capecitabine 1000 mg/m2 twice daily (days 1–14), respectively, followed by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
5
35
1
Order By: Relevance
“…However, PERFECT trail suggested that the combining nCRT with immunotherapy didn't show satisfactory database in patients with EAC (30). In addition, many trails also evaluated the clinical result of neoadjuvant immunotherapy in locally advanced EC patients, and the security of treatment was also analyzed (12,(35)(36)(37)(38)(39)(40). The MPR and pCR for ESCC patients, received surgery, were 52.9%-72.0% and 30.2%-50.0% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PERFECT trail suggested that the combining nCRT with immunotherapy didn't show satisfactory database in patients with EAC (30). In addition, many trails also evaluated the clinical result of neoadjuvant immunotherapy in locally advanced EC patients, and the security of treatment was also analyzed (12,(35)(36)(37)(38)(39)(40). The MPR and pCR for ESCC patients, received surgery, were 52.9%-72.0% and 30.2%-50.0% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Neo-PLANET trail suggested that neoadjuvant camrelizumab plus nCRT exhibited pCR rate was 33.3% and MPR rate was 44.4% in patients with locally advanced EAC patients, with an acceptable safety profile. Although didn’t reach final survival outcome, Two-year progression free survival (PFS) and over survival (OS) rates were 66.9% and 76.1%, respectively ( 13 ). However, PERFECT trail suggested that the combining nCRT with immunotherapy didn’t show satisfactory database in patients with EAC ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that neoadjuvant therapy can effectively improve the clinical outcomes of EGC patients such as large clinical trials CheckMate 577 [12], PRODIGY [13], and CROSS [14]. Combined neoadjuvant immunotherapy and chemoradiotherapy have also demonstrated favorable efficacy and safety [15]. However, whether neoadjuvant therapy affects the number of dissected LNs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no indication for camrelizumab in GC, camrelizumab in combination with chemotherapy in first-line therapy of GC followed by camrelizumab plus apatinib maintenance therapy achieved favorable results in phase II study ( 7 ). There has also been recent clinical study ( 8 ) of neoadjuvant camrelizumab plus concurrent chemoradiotherapy exhibits promising pathological response in patients with locally advanced gastric adenocarcinoma, with an acceptable safety profile.…”
Section: Introductionmentioning
confidence: 99%